2001
DOI: 10.1046/j.1442-200x.2001.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhalation and nitric oxide synthase inhibitor supplement for endotoxin‐induced hypotension

Abstract: Nitric oxide inhalation alone carries a potential risk of further lowering systemic arterial pressure in a piglet with hypotension induced by endotoxin, whereas the combined therapy resulted in the recovery of the blood pressure to pre-endotoxin levels. The combined therapy was simultaneously effective against pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…It is worth noting that increased pressure in pulmonary circulation during sepsis is associated with a reduced patient survival [ 13 ]. Numerous studies besides our own have shown that administration of inhaled NO may normalize increased pulmonary arterial pressure [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that increased pressure in pulmonary circulation during sepsis is associated with a reduced patient survival [ 13 ]. Numerous studies besides our own have shown that administration of inhaled NO may normalize increased pulmonary arterial pressure [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings show partially beneficial effects and suggest that this approach deserves further evaluation (11, 12). However, it is not known whether NOS blockade, in hemodynamically stable lung injury, is associated with improved oxygenation with NO inhalation.…”
Section: Introductionmentioning
confidence: 87%
“…Prior studies on the effects of combined treatment, with blockade of NOS and NO inhalation, have been reported on both neonatal and adult models of experimental sepsis and endotoxemia (10-12), where recovery of the systemic blood pressure by blockade of NOS and simultaneous attenuation of pulmonary hypertension by NO inhalation were targeted. The findings show partially beneficial effects and suggest that this approach deserves further evaluation (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…L-NAME) or an iNOS inhibitor (aminoguanidine) is deleterious, but the use of N w-nitro-L-arginine (L-NNA) prevents hypotension. [106][107][108] These investigations are inconclusive as to the role of NO in sepsis-induced hypotension. Use of an angiotensin receptor 2 antagonist alone or with a bradykinin B2 receptor antagonist may be beneficial in sepsis.…”
Section: Summary and Implications For Therapymentioning
confidence: 99%